2015
DOI: 10.1017/s0950268815002150
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus diversity in children with gastroenteritis in South Africa from 2009 to 2013: GII.4 variants and recombinant strains predominate

Abstract: From 2009 to 2013 the diversity of noroviruses (NoVs) in children (⩽5 years) hospitalized with gastroenteritis in South Africa was investigated. NoVs were genotyped based on nucleotide sequence analyses of partial RNA-dependent RNA polymerase (RdRp) and capsid genes. Seventeen RdRp genotypes (GI.P2, GI.P3, GI.P6, GI.P7, GI.P not assigned (NA), GI.Pb, GI.Pf, GII.P2, GII.P4, GII.P7, GII.P13, GII.P16, GII.P21, GII.Pc, GII.Pe, GII.Pg, GII.PNA) and 20 capsid genotypes (GI.1, GI.2, GI.3, GI.5, GI.6, GI.7, GI.NA, GII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Norovirus GII was the dominant circulating genogroup detected (n = 17: 77.2 %). This finding is consistent with most studies worldwide, including those from Africa, in which NoV GII was reported to be predominantly responsible for gastroenteritis outbreaks and sporadic cases [3,6,21,22,29,49,53,54]. Nucleotide sequence and phylogenetic analysis of the NoV GII strains revealed that GII.17 NoVs comprise the predominant genotype (36.4 %) detected in this study.…”
Section: Genogrouping/genotyping Of Human Enteric Virusessupporting
confidence: 92%
See 1 more Smart Citation
“…Norovirus GII was the dominant circulating genogroup detected (n = 17: 77.2 %). This finding is consistent with most studies worldwide, including those from Africa, in which NoV GII was reported to be predominantly responsible for gastroenteritis outbreaks and sporadic cases [3,6,21,22,29,49,53,54]. Nucleotide sequence and phylogenetic analysis of the NoV GII strains revealed that GII.17 NoVs comprise the predominant genotype (36.4 %) detected in this study.…”
Section: Genogrouping/genotyping Of Human Enteric Virusessupporting
confidence: 92%
“…The role of NoVs and SaVs as causative agents of gastroenteritis and their diversity in Africa is not well studied, except in some reports from a few African countries [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. There has been only one published study from Ethiopia regarding the presence and genetic diversity of NoVs [37], and none for SaVs to date.…”
Section: Introductionmentioning
confidence: 99%
“…This novel GII.P16-GII.2 recombinant virus caused at least seven outbreaks in the United States in 2016 as early as August. While GII.P16 polymerases associated with different GII capsids have circulated for decades (17,18,42,(49)(50)(51)(52)(53)(54) and caused occasional outbreaks (16,55,56), the GII.P16 polymerase associated with GII.4 Sydney and GII.2 genotypes appears to have made these viruses evolve toward greater transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Continued Continued recombination breakpoints have been identified across the norovirus genome, they are most frequently found in the ORF1-ORF2 junction region [29][30][31][32][33][34][35][36]. Dual typing (ORF1-RdRp=P type, ORF2=genotype) is now used routinely in many laboratories worldwide and at least 14 GI P-types and 27 GII P-types as well as 9 GI capsid genotypes and 22 GII capsid genotypes have been described [2,19,27].…”
Section: Introductionmentioning
confidence: 99%